A Numerical Study Of P-Cuo/N-Azo/ Thin Film Solar Cells Metal Oxide Based Scaps 1-D - Zulfadli Pelawi; H. Alam (Jurnal Info Sains : Informatika dan Sains, 2023)
In this paper described a photovoltaic characteristics of thin film heterojunction solar cells comprising p-CuO/n-AZO were conducted numerically using a solar cell capacitance simulator (SCAPS-1D). The solar cells device performance p-CuO/n-AZO metal oxide based was investigated, in terms of different n-AZO parameters such as the thickness and carrier concentration. The simulation results indicate that the highest efficiency attain to 9 %, by setting n-AZO thickness and carrier concentration of 50 nm, and 5.0x1018 cm-3 respectively. According to the results obtained, we conclude that the presented thin film solar cell device simulation model using SCAPS 1-D tools could be a part of the solar cell classes with potential promise for photovoltaic applications